Management of bruxism associated with temporomandibular disorder: case report - Marcus Vinícius Andrade OLIVEIRA; Marco Aurélio Fonseca PORTO; Paulo Cézar SIMAMOTO JÚNIOR; Uriel Paulo COELHO; Luana Cardoso CABRAL (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Studies have found the association between episodes of bruxism and the presence of signs and symptoms of temporomandibular disorder (TMD). The aim of the present study was to report the diagnosis and palliative therapy of bruxism associated with TMD. Patient, 23 years old, male gender, presented at dental clinic, complaining of pain in the temporomandibular joint on the left side and alteration of the form of the anterior teeth. During the anamnesis it was documented that this symptom was recurrent and reported the habit of grinding teeth. The clinical examination observed discrepancy between the centric relation and the maximum habitual intercuspation, unsatisfactory protrusive guide, presence of wear facets, clicking and mandibular deviation during mouth opening. The Research Diagnostic Criteria for Temporomandibular Disorders (RDC / TMD) questionnaire was applied to diagnose TMD. By means of specific algorithms this disorder was classified as myofascial pain, disc displacement with reduction and osteoarthritis, all affecting the left side. Thus, it was proposed the assembly of the models in semi-adjustable articulator for occlusal mapping and waxing diagnosis, then the occlusal adjustment by selective wear and material addition was executed. After this procedure, the occlusal splint was installed as a palliative therapy for bruxism. This case report suggests that the dental approach by means of occlusal adjustment and occlusal splint, in a patient diagnosed with bruxism and temporomandibular disorder, reduces the signs and symptoms that affect the components of the Stomatognathic System.